Thermodynamics guided ultrafast and continuous preparation of Mo2C nanocrystals for hydrogen evolution electrocatalysis - Hu Sun; Guanghui Li; Jun Luo; Mingjun Rao; Zhiwei Peng; Tao Jiang (Materials & Design, 2020)
Existing nano-Mo2C preparation methods suffer from expensive raw materials, subtle operation demands and complex synthesis steps. Herein, both theoretical and experimental studies were performed to develop a more efficient and economical method for nano-Mo2C preparation. Reaction thermodynamics of gas-vapor system of CH4-MoO3-N2 indicates that high-proportion inert gas significantly increases the required carbonization potential (CO/CO2) for Mo2C formation, but surplus carbon produced from methane decomposition can trigger water gas producing reaction and Boudouard reaction to help meet the requirement. Nano-Mo2C was then synthesized by mixing N2-carried MoO3 vapor with CH4 under varying conditions including temperature, gas flowrate and vapor concentration. It is found that MoO3 vapor experienced conversions to monoclinic MoO2 to cubic Mo to hexagonal Mo2C, and all these stages could be finished in as short as about 6 s at 1100 °C with initial molar ratio of CH4 to MoO3 over 3.5. The final products were present as porous plate-like single crystals or chain-like polycrystals, which are determined by initial vapor concentration and gas flowrate. Furtherly, electrocatalytic properties of Mo2C nanocrystals for hydrogen evolution reaction were measured, and the sample with the largest specific surface area and cleaner surface showed competitive performance over reported nano-Mo2C.